CAMPURAN TERIGU DAN SAGU SEBAGAI EKSTENDER PEREKAT KAYU LAPIS - Suwardi Sumadiwangsa (Jurnal Penelitian Hasil Hutan, 1986)
In  1983 Indonesian plywood    industries  consumed  about  45 000 tons  of  wheat flour  as an extender  of  ureaformaldehyde   adhesive. This material is imported from foreign  country,  although Indonesia,  as an agricultural country,  is rich with carbohydrate  resources such as palm trees.The result of a laboratory study on the effect of four wheat and sago flour  mixtures and four  levels of extender content on plywood  property is presented  in this paper.The mixtures of  wheat and sago flour  were 100/0, 80/20, 60/40, and 40/60. Each of them  was mixed  with the UF glue at four  different composition,   namely  I 5, 20, 25, and 30 percent  of each total glue weight.The experiment  was based on the 4 x 4 factorial  design  with. 4 replications.The result shows that the wheat and sago flour  mixture  does not significantly  affect  the glue shear as well as the wood failure.  The extender content on the other hand, affects significantly  the above properties,  in which higher extender content has resulted in lower plywood  quality.  The study  reveals also that all of the plywood  samples  tested conform  with the Indonesian  Standard  (Sil) for  plywood  type II.